1998
DOI: 10.1021/ja981644y
|View full text |Cite
|
Sign up to set email alerts
|

Study of Substituent Effects on the Photoconductivity of Soluble 2,(3)- and 1,(4)-Substituted Phthalocyaninato- and Naphthalocyaninatotitanium(IV) Oxides

Abstract: Soluble alkyl (II, 8a,b), fluoroalkyl (4a), and fluoroalkoxy (4b,c, 8c) 1,(4)- or 2,(3)-substituted phthalocyaninato- and linear 2,(3)- and angular 1,(2)-annulated naphthalocyaninatotitanium(IV) oxides 10, 12, and 14 were synthesized and characterized with regard to their spectroscopic, photophysical, and photochemical properties. While alkyl- and fluoroalkoxy-substituted compounds are highly soluble in nonpolar solvents, e.g., hexane, fluoroalkyl-substituted compounds are better soluble in polar aprotic solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 44 publications
2
39
0
1
Order By: Relevance
“…7), a weak band at $681 nm and a shoulder at $622 nm are observed (trace b). This is very similar to what is reported in the literature for Pc-Ti(O) [29]. The absorption spectrum of the electrolyte (Fig.…”
Section: Redox Properties Of Adsorbed 2 Andsupporting
confidence: 90%
“…7), a weak band at $681 nm and a shoulder at $622 nm are observed (trace b). This is very similar to what is reported in the literature for Pc-Ti(O) [29]. The absorption spectrum of the electrolyte (Fig.…”
Section: Redox Properties Of Adsorbed 2 Andsupporting
confidence: 90%
“…Electron-withdrawing substituents at the periphery of the macrocycle cause a large increase in the ionization potential of the system, protect the MPc from oxidative destruction [15][16][17], and thus enhance its catalytic activity. From the viewpoint of organic semiconductors, it is known that substitution of electron donor and acceptor groups leads to p-type and n-type characteristics of the Pc ring, respectively [7,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The binuclear complex displayed a positive nonlinear absorption coefficient. It is found that the linear optical properties were little changed but the optical limiting effectiveness of the binuclear fused phthalocyanine 1 is lower relative to tBu 4 The versatility of Pc synthetic organic chemistry [21,22] has led to a large variety of Pc structures differing in the number, nature and position of peripheral substituents, [23][24][25][26][27] with various coordinating central atoms, [17] axial ligands, [28,29] and with a variable number of linkages between Pc rings in oligomeric [30,31] or polymeric species. [32] Among the many possibilities for varying the Pc structure, the expansion of the π-electron system through the synthesis of naphthalocyanines (Ncs) is the most common.…”
Section: Introductionmentioning
confidence: 99%